Gains from Early Support of a New Political Party - Marco Leonardi; Rossella Mossucca; Fabiano Schivardi; Battista Severgnini (Institute of Labor Economics (IZA), 2019)
We study the potential benefits and mechanisms of firms' political connections by analyzing the Italian experience, where, in the early nineties, Silvio Berlusconi, a rich TV tycoon, became the leader of the conservative political coalition. Using firm-level data, we find that the 101 companies supporting Berlusconi's successful bid to become prime minister did better than controls in terms of sales and employment but not of productivity. The results are confirmed when we instrument the decision to support Berlusconi with electoral outcomes in the 1921 elections. We also find suggestive evidence that the supporters' superior performance is stronger in sectors with high external financial dependence and high advertising intensity.
Keywords: G32; G38; D72; 330; political connections; productivity; policy regulation